2015
DOI: 10.3892/ol.2015.3230
|View full text |Cite
|
Sign up to set email alerts
|

Lugol chromoendoscopic screening for esophageal dysplasia/early squamous cell carcinoma in patients with esophageal symptoms in low-risk region in China

Abstract: Abstract. Detection of esophageal dysplasia/early esophageal squamous cell carcinoma (ESCC) is essential for improving 5-year survival. The aim of this prospective study was to evaluate whether Lugol chromoendoscopy improves the detection of esophageal dysplasia/early ESCC in patients with esophageal symptoms in a low-incidence region in China. Eligible patients were randomly assigned into two groups who received routine endoscopy or Lugol chromoendoscopy. During endoscopy, between one and five biopsies were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“… 26 In another endoscopic screening study, 37% of the LVL > 10 mm showed dysplasia or neoplasia compared with only 5% of the LVL between 5 and 10 mm. 17 In our study, all ESPTs were ≥20 mm, whereas the six non-dysplastic lesions had a median diameter of only 6 mm. Therefore, we would suggest follow-up with repeat EGD or biopsy instead of ER in esophageal lesions smaller than 20 mm.…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“… 26 In another endoscopic screening study, 37% of the LVL > 10 mm showed dysplasia or neoplasia compared with only 5% of the LVL between 5 and 10 mm. 17 In our study, all ESPTs were ≥20 mm, whereas the six non-dysplastic lesions had a median diameter of only 6 mm. Therefore, we would suggest follow-up with repeat EGD or biopsy instead of ER in esophageal lesions smaller than 20 mm.…”
Section: Discussionmentioning
confidence: 43%
“… 13 An endoscopic screening study by Shao et al , found that 74% of the LVL showed no dysplasia on histopathological assessment. 17 Another endoscopic screening study in patients with HNSCC showed that 82% of the LVL were non dysplastic. 26 A high false positive detection rate is also reflected by our results: 46% of lesions that were suspicious on LCE were false positive, compared with 14% in NBI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lugol chromoendoscopy is a procedure in which Lugol's iodine is instilled into the gastrointestinal tract at the time of endoscopy. According to a study, the detection rate of esophageal dysplasia and early ESCC was 13.7% in the group of patients who underwent chromoendoscopy compared to 10.6% in the group of patients who underwent routine endoscopy ( p = 0.003) [ 13 ]. We did not perform lugol chromoendoscopy for our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Areas with glycogen depletion such as dysplasia, squamous cell carcinoma, Barrett's epithelium, and inflammation remain unblemished or weakly stained (14) . Chromoendoscopy with Lugol's solution has improved the detection rate of squamous dysplasia and squamous cell carcinoma in early stages in patients with esophageal symptoms (reflux symptoms, dysphagia and globus sensation) compared to conventional endoscopy in both high-risk population and low risk-population (15,16) . In the study published by Shiozaki et al 178 patients with head and neck cancer were screened for synchronous and metachronous primary esophageal cancer using chromoendoscopy with Lugol's solution.…”
Section: Discussionmentioning
confidence: 99%